Charakter prawny stosunków kredytu bankowego - Janiak, Andrzej (Wydział Prawa i Administracji UAM, 1983)
The author makes an attempt at determining the dispute on legal character of bank credit relations which has been under way for years in the Polish legal literature. The proposition set forth mainly in literature of financial law alleging that bank credit relations under conditions of the socialized economy reveal traits characteristic of administrative law is polemized with. Multiaspectual analysis of binding regulation of crediting units of socialized economy allows for the conclusion that bank credit relations are posessing all the attributes of the obligational relations of civil law. That judgement of legal character of bank credit relations is not resulting only from analysis of the legal regulation. In the opinion of the author it is the only acceptable one also in the light of the position of enterprises as independent, self governing and self supporting economic subjects.
Legal character of bank credit relations